Penggunaan Media Digital Dalam Pengajaran Pendidikan Agama Islam - Hasibuan, Sulhan Efendi; Rambe, Sofia Marini; Nasution, Nurlan Saima; Ritonga, Fadhilah Khairany (Jurnal Pendidikan dan Dakwah, 2024)
The use of digital media in teaching Islamic Religious Education (PAI) has become an important movement in education, especially in the era of increasingly advanced information technology. This article uses the literature review method to explore various forms and benefits of using digital media in PAI teaching. This research highlights how digital media can increase learning effectiveness, enrich teaching materials, and motivate students to study Islamic religious education. The study results show that using digital media, such as interactive learning applications, educational videos, e-learning platforms, and social media, can make learning more interesting and dynamic. Digital media also allows access to a wider and more varied range of learning resources and supports independent learning for students. Additionally, integrating digital media in PAI teaching can help teachers deliver material more creatively and efficiently. This research concludes that using digital media in PAI teaching has great potential to improve the quality of Islamic religious education. Adequate training and support are needed for teachers to optimize the use of digital media. Hopefully, these findings can provide insight for educators and policymakers in developing more innovative and effective Pal teaching strategies in the future.